Relação família-escola: uma parceria para a inclusão de alunos com altas habilidades/superdotação - Rech, Andréia Jaqueline Devalle (2016)
School inclusion has been a challenge for many teachers who work on regular school classrooms. A number of factors hinder the pedagogical practice of these teachers in their teaching with students who are the target audience of special education. Besides, it is observed that, when dealing with school inclusion of gifted and talented students (G/T), there is resistance from some teachers. This fact lies on the lack of knowledge about the theme of G/T, which may occur due to the wrong conceptions socially widespread, adding to that an incipient initial education in relation to G/T students. Accordingly, it is necessary to create support networks so that school inclusion of G/T students becomes effective. In this sense, the family could be a support network and set up a partnership with the school. Thus, both can articulate and organize a collaborative work on behalf of school inclusion of the G/T child. After reflecting about the situation exposed, this study proposes the following thesis: school inclusion of the G/T child can be effective when family and school act in conjunction in this process, eliminating/diminishing the barriers that hinder this partnership, since the family can influence the school inclusion of the G/T child. This study included 12 families with children identified as G/T more than a year ago, and regularly attended the Giftedness Incentive Program (GIP) during the year of 2014, seven special educators, six teachers from early grades and five counseling teachers that, in the year of 2015, worked with G/T students. Regarding the method, the study case within the qualitative approach was chosen. The instruments of data collection selected were: narrative interview, Questionnaire of Family System Characterization Version – Parents or Guardians (DESSEN, 2011), Checklist of Shared Routine and Engagement between Family-school, Version for Teachers, and Checklist of Shared Routine and Engagement between Family-school, Version for Parents (mother, father, or guardian), both validated by Dessen and Polonia (2011). The interviews were analyzed qualitatively and from the analysis of frequency, through categories already defined by the authors of the instrument. The final considerations point to a relation between family and school that is still incipient, due to the fact that some barriers/constraints were identified, having prevailed an accusative relationship, which may be hindering the construction of a partnership relation. There were specific cases in which there was conjunction between both institutions, and that result in greater influence/participation of the family in the school life of the G/T child. Therefore, the study raises the need to offer continuous education for both the family and the school, aiming at broadening the debate regarding the importance that both have in creating a support network so that, together, they can articulate actions on behalf of school inclusion of the child who is also a G/T student.